Optimalisasi Fungsi Rumah Sebagai Tempat Pembinaan Warga Gereja di Masa Pandemi Covid-19 - Purim Marbun (DIEGESIS: Jurnal Teologi Kharismatika, 2020)
This writing is motivated by the problem of the lack of church members who use the house as a place of spiritual formation. This is due to the lack of family skills in carrying out coaching tasks both practically and theologically. Another problem is that many coaching programs are centered in the church, thus consuming family time. During the Covid-19 Pandemic, it was necessary to attend church from home in accordance with government recommendations. By using a qualitative approach, and using a descriptive analysis study research method, accompanied by a descriptive analysis study it was found that the house can be used as a place for the formation of church members. Optimization of the house as a place for fostering church members is done by expanding the dimensions of the function of the house that is not only a place to live but as a place to educate, a place of worship and the ongoing community of faith.Â AbstrakTulisan ini dilatarbelakangi adanya masalah minimnya warga gereja yang memanfaatkan rumah sebagai tempat pembinaan rohani. Hal ini disebabkan kurangnya ketrampilan keluarga melakukan tugas-tugas pembinaan baik secara praktis maupun teologis. Masalah yang lain adalah banyaknya program pembinaan yang berpusat di gereja, sehingga menyita waktu keluarga. Dalam masa Pandemi Covid-19, mengharuskan bergereja dari rumah sesuai dengan anjuran pemerintah. Dengan menggunakan pendekatan kualitatif, dan memakai metode penelitian studi deskriptif analisis, disertai dengan kajian analisis deskriptif didapati bahwa rumah dapat dijadikan sebagai tempat pembinaan warga gereja. Optimaliasasi rumah sebagai tempat pembinaan warga gereja, dilakukan dengan cara memperluas dimensi fungsi rumah yang bukan saja sebagai tempat tinggal, melainkan sebagai tempat mendidik, tempat beribadah dan berlangsungnya komunitas iman.